EDUKASI PENGETAHUAN TENTANG PROPER BODY MECHANICS UNTUK MENGURANGI NYERI LOW BACK PAIN (LBP) PADAKOMUNITAS PERSIT KARTIKA CHANDRA KIRANA KORAMIL JEBRES - Syarifah Syarifah; Sulistiyani Prabu Aji; Noviyati Rahardjo Putri (Rena Cipta Mandiri, 2025)
Lower back pain (Low Back Pain or LBP) is one of the most common musculoskeletal complaints experienced by women, especially those involved in household activities or caring for toddlers. Activities such as bending, lifting loads, or non-ergonomic breastfeeding positions are major risk factors. Based on this, education about